New building in old cities writings by Gustavo Giovannoni on architectural and urban conservation - Giovannoni, Gustavo 1873-1947 (Getty Conservation Institute, 2024)
"This illustrated critical anthology presents in English translation selected writings by the Italian architect, historian, and restorer Gustavo Giovannoni (1873-1947)"--
Includes bibliographical references (p. 376-383) and index
Keywords: Giovannoni, Gustavo -- 1873-1947; Geschichte 1903-1947; Konservierung; Schrifttum; Städtebau; Stadtplanung; Wiederaufbau; Architektur; Architecture / Conservation and restoration; Monuments / Conservation and restoration; Historic districts / Conservation and restoration; Urban renewal; City planning; Architecture / Conservation et restauration; Monuments / Conservation et restauration; Quartiers anciens / Conservation et restauration; Rénovation urbaine; urban renewal; ARCHITECTURE / General; Aufsatzsammlung